Interpretation of coastal sediment quality based on trace metal and PAH analysis, benthic foraminifera, and toxicity tests (Sardinia, Western Mediterranean). Issue 1 (15th May 2015) - Schintu, Marco; Buosi, Carla; Galgani, François; Marrucci, Alessandro; Marras, Barbara; Ibba, Angelo; Cherchi, Antonietta
Highlights: The results raise questions concerning the validity of sediment quality guidelines. The toxicity rate was significant in many samples. Foraminifera have given similar indications for chemical analysis. Abstract: An integrated approach for the assessment of coastal sediment quality was utilised in three areas of Sardinia (Western Mediterranean, Italy). Sediments were analysed for trace metals and polycyclic aromatic hydrocarbons (PAHs), while benthic foraminifera were used as bioindicators. Furthermore, the embryo-toxicity test was used to provide ecologically relevant information using rapid and cost-effective screening tools. The aim was to evaluate the usefulness of coupling different analytical tools. The results revealed the presence of polluted sediments in areas exposed to petrochemical industries, smelters or military settlements. However, while foraminifera have presented similar indications for chemical analysis of contamination levels in the different areas, the toxicity test exhibited a poor relationship with the contaminants measured individually. The results raise questions concerning the bioavailability of contaminants released by sediments in the water column. Overall, the toxicity rate was significant in many samples in comparison with other sites studied in other Mediterranean regions.